Flotation of sylvinite from Thakhek, Lao, P.D.R. - Chairoj Rattanakawin; Woraruethai Lakantha; Ittirit Kajai (Songklanakarin Journal of Science and Technology (SJST), 2019)
The purpose of this research is to study about sylvinite flotation. Both chemical and operating variables are main factors in this cationic flotation study. The chemical factors consist of mineralogy, solubility, amine dosages and types of frothers: pine oil and MIBC added. The operating factors, controlling flotation kinetics, compose of particle size, agitation intensity and conditioning time. Mineral characterization was carried out using XRD technique. From the XRD trace, both sylvite (KCl) and halite (NaCl) are major minerals. Therefore, a sampled potash ore from Thakhek, Lao, P.D.R. can be characterized as sylvinite. And ore solubility is 84.2 g/100 g water at 34oC. Chemical analysis of this ore was conducted using AAS technique. It is coincide with the mineralogical analysis that KCl and NaCl are the major components with some minor KCl·MgCl2·H2O. Both grade and recovery of the rougher concentrates were used to measure the flotation efficacy. Chemically, an optimum flotation of sylvinite in the saturated brine with amine and MIBC was found at the dosages of 150 and 50 g/ton ore respectively, yielding 41.5% K2O with 95.9% recovery. Operationally, an optimum flotation of 30-mesh sylvinite with the indicated amine and MIBC dosages at the agitation intensity of 1000 r.p.m and 9-minute conditioning time yields 39.1% K2O with 94.2% recovery. Furthermore, the flotation kinetics follows the first-order rate law with rate constant of 1.41 sec-1 . Suggested that direct cleaner and/or re-cleaner flotation with reagent combinations of both collector and frother, or reverse flotation of the retaining halite using alkyl morpholine as a collector could enhance the final concentrate grade up to 60% K2O complying with the fertilizer industry.